Analysis of Pilot Projects and Its Guidelines for Paris Agreement Article 6 - Kim, Jieun; Kim, Ji-Hyun; Park, Hyemin (Journal of Environmental Policy and Administration, 2021)
While the Kyoto Mechanism ended in 2020 and Article 6 of the Paris Agreement is under negotiation, international organizations and developed countries are designing and implementing the Article 6 pilot project. This study analyzes how each provision of Article 6 is interpreted and applied in three examples of pilot projects, with a particular focus on “sustainability,” one of the primary values emphasized in Article 6 of the Paris Agreement. To this end, this study analyzed how the African Development Bank, the Swedish Energy Agency, and the Swiss KliK Foundation interpreted and implemented each provision of the three main frameworks of Article 6, namely the cooperative approach (Article 6.2), the international trading mechanism on the reduction outcome under COP (Article 6.4), and the non-market approach (Article 6.8). As a result, the pilot projects reflected the core values of considering internationally transferred mitigation outcomes (ITMO), developing a baseline methodology, promoting environmental integrity, and the sustainable development of the host country. Under the new Korean NDC, which increased the portion of overseas reduction, either the government planning a project under Article 6.2 or a company planning a project under Article 6.4 should selectively apply the trials and considerations from the preemptive pilots of Article 6 analyzed in the study. KCI Citation Count: 0